Investigation of Chromium(III)-Picolinate Adsorption on Some Soil Types - Szegvári, Ildikó; Prokisch, József; Simon, László; Vár, László (Acta Agraria Debreceniensis, 2003)
In the experiment adsorption characteristics of different soil types (humic sand, meadow soil, leached chernozem and meadow solonec) was examined on the basis of adsorption isotherms for Cr(III)-picolinate. The Langmuir equation was used to describe the isotherms by which the amounts of metal ions actually and maximally adsorbed by the soils were determined concerning the given complex. A comparison was made among the organically bound Cr(III)-picolinate, an inorganic Cr(III) compound and a Cr(VI) form examined in a previous study. Based on the adsorption isotherms, adsorption capacity of the Cr(III)-picolinate was found 20 times smaller on sandy soil and 50 times smaller on the chernozem comparing to that of the inorganic Cr(III)-chloride, thus, the bio-availability of the chromium for the plants is 20 and 50 times higher in case of the given soil types. For the well-known toxic Cr(VI)-form, the adsorption was 2 times higher in case of sandy soil and 5 times higher for chernozem than in case of the organic Cr(III)-complex compound.